Performance Measurement of the National Amil Zakat Agency (BAZNAS) Kediri Regency Using the Maslahah Performa (MaP) Approach - Nurflorenza, Bilqis Tata; Mubarrok, Ujang Syahrul (UNIVED Press, 2026)
This study aims to analyze and assess BAZNAS's operations performance in Kediri Regency, using the Maslahah Performa (MaP) framework. The main issue addressed in this research is the importance of examining not only financial and management efficiency but also how well the objectives of maqasid shariah are achieved in zakat management. Using a qualitative descriptive approach with a normative-sociological viewpoint, the research gathered information through observations, interviews, and document reviews. The results indicate that BAZNAS Kediri shows a strong level of Maslahah Performa (MaP), achieving a performance score of 0.941, indicating significant success in meeting the welfare needs of stakeholders across six critical areas: worship, internal processes, human resources, learning, customer relations, and asset management. On the other hand, the process-oriented score of 0.550 indicates that although the execution of the Maslahah Scorecard (MaSC) stages is satisfactory, further improvements are needed to achieve optimal results. In summary, the Maslahah Performa method is an effective assessment tool for evaluating zakat institutions by combining financial and spiritual elements, thereby enhancing overall accountability and promoting sustainable performance.